2023
DOI: 10.5603/rpor.a2023.0017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of postoperative and definitive (chemo)radiotherapy in sinonasal carcinoma. Adult Comorbidity Evaluation 27 score as a predictor of survival

Abstract: Background:The objective was to evaluate the efficacy and toxicity of curative radiotherapy in patients with sinonasal carcinoma and to identify prognostic factors influencing treatment outcomes. Materials and methods:The authors conducted a retrospective study of 61 consecutive patients treated with postoperative or definitive radiotherapy from 2002 to 2018 (median age 59 years, current/former smokers 71%, maxillary sinus 67%, nasal cavity 26%). The majority of patients were diagnosed with locally advanced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Due to heterogeneity, it is important to report detailed information about pa- In this study, the primary site of most tumors was maxillary sinus (26 out of 28 patients). Although nasal cavity is the most common primary site in many studies [4], maxillary sinus tumors are more prevalent in some studies that reported only sinonasal cancer patients who were treated with radiotherapy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to heterogeneity, it is important to report detailed information about pa- In this study, the primary site of most tumors was maxillary sinus (26 out of 28 patients). Although nasal cavity is the most common primary site in many studies [4], maxillary sinus tumors are more prevalent in some studies that reported only sinonasal cancer patients who were treated with radiotherapy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Because of rarity and heterogenicity of these tumors, we cannot rely on randomized clinical trials to determine the best management approach, and single-institution retrospective studies provided most of the available data [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%